Mapping Research on Premarital Sexual in Indonesia: A Bibliometric Review of the Literature Over Two Decades - Qariati , Nurul Indah; Salim, Lutfi Agus; Indriani , Diah (Journal of Ecohumanism, 2025)
Engaging in premarital sexual activities can have both global and long-term impacts. Adolescents are particularly vulnerable to unintended pregnancies, unsafe abortions, maternal and fetal deaths, HIV/AIDS, hemorrhaging, premature births, and the emergence of stunted generations. Such behaviors obstruct Indonesia's demographic dividend, necessitating both preventative and corrective measures to address premarital sexual activity. This study aims to identify trends and visualize literature on premarital sexual activity over the past two decades, identify keywords for future research on the topic, and profile researchers with the highest number of articles and citations in the last two decades. The Scopus database served as the source for this study’s metadata, collected on June 5, 2024, with data analyzed using Bibliometrix software. A strict selection process identified 902 articles, which were filtered down to 42 for in-depth analysis. The findings reveal essential topics within premarital sexual research, offering a quantitative analysis presented through images and tables. The highest number of publications over the two decades was recorded in 2020. The author with the highest citation count was N.K. Fauk, while Nurmala was identified as the most productive researcher. New keywords emerging in 2023 include "father," "social norm," "unintended pregnancy," and "concept of adultery." These insights provide valuable guidance and opportunities for researchers in developing future research directions and practical implications for educators and policymakers in designing more effective and targeted prevention strategies.